The MAP3K-Coding QUI-GON JINN (QGJ) Gene Is Essential to the Formation of Unreduced Embryo Sacs in Paspalum - Mancini, Micaela; Permingeat, Hugo; Colono, Carolina; Siena, Lorena; Pupilli, Fulvio; Azzaro, Celeste; de Alencar Dusi, Diva Maria; de Campos Carneiro, Vera Tavares; Podio, Maricel; Seijo, José Guillermo; González, Ana María; Felitti, Silvina A.; et al. (Frontiers in Plant Science, 2018)
Apomixis is a clonal mode of reproduction via seeds, which results from the failure of meiosis and fertilization in the sexual female reproductive pathway. In previous transcriptomic surveys, we identified a mitogen-activated protein kinase kinase kinase (N46) displaying differential representation in florets of sexual and apomictic Paspalum notatum genotypes. Here we retrieved and characterized the N46 full cDNA sequence from sexual and apomictic floral transcriptomes. Phylogenetic analyses showed that N46 was a member of the YODA family, which was re-named QUI-GON JINN (QGJ). Differential expression in florets of sexual and apomictic plants was confirmed by qPCR. In situ hybridization experiments revealed expression in the nucellus of aposporous plants’ ovules, which was absent in sexual plants. RNAi inhibition of QGJ expression in two apomictic genotypes resulted in significantly reduced rates of aposporous embryo sac formation, with respect to the level detected in wild type aposporous plants and transformation controls. Although the QGJ locus segregated independently of apospory, a related long non-coding RNA sequence (PN_LNC_QGJ) is transcribed from the Paspalum apospory-controlling region (ACR) in florets of apomictic plants only. Upregulation of PN_LNC_QGJ in florets of apomictic plants is correlated with a higher representation of homologous sRNAs. Our results indicate that the activity of QGJ in the nucellus of apomictic plants is necessary to form non-reduced embryo sacs and that a long non-coding sequence with regulatory potential is located within the ACR.